2014
DOI: 10.1002/admi.201300115
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Solid‐Electrolyte‐Interphases on Sn (100) and (001) Electrodes Studied by Soft X‐Ray Spectroscopy

Abstract: Soft X‐ray absorption spectroscopy with different probe depth was employed to characterize the solid electrolyte interphases (SEIs) formed on β‐Sn single crystals with two different surface orientations. Based on comparative studies of C‐K, O‐K, and F‐K absorption spectra between the SEIs and reference samples, SEI on Sn (100) mainly consists of porous Li2CO3 species with electrolyte uptake, while SEI on Sn (001) essentially consists of LiF and organic molecules, with a small amount of –CO3 and electrolyte bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
103
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 49 publications
6
103
0
Order By: Relevance
“…During electrochemical cycling, valence states as well as the local geometric environment undergo changes due to the diffusion of lithium and other elements in the material. Based on this theoretical prediction, lithium secondary batteries have been intensively studied with the use of XAFS to find out what happens during the process, including electrochemical reaction, formation of interfaces between electrodes and electrolytes . In this section, the study of electrochemical reactions as well as degradation mechanisms of lithium secondary batteries will be introduced and summarized with a focus on the application of XAFS.…”
Section: X‐ray Absorption Fine Structure and Applicationsmentioning
confidence: 99%
“…During electrochemical cycling, valence states as well as the local geometric environment undergo changes due to the diffusion of lithium and other elements in the material. Based on this theoretical prediction, lithium secondary batteries have been intensively studied with the use of XAFS to find out what happens during the process, including electrochemical reaction, formation of interfaces between electrodes and electrolytes . In this section, the study of electrochemical reactions as well as degradation mechanisms of lithium secondary batteries will be introduced and summarized with a focus on the application of XAFS.…”
Section: X‐ray Absorption Fine Structure and Applicationsmentioning
confidence: 99%
“…[19][20][21] Interestingly, recent model studies on Sn single crystal electrodes in organic carbonate electrolytes revealed a strong correlation between the crystal surface orientation and the SEI composition. 22,23 A similar study of the composition of the SEI on a silicon monocrystal electrode showed strong effects of different SEI formation protocols, presence/absence of intrinsic SiO 2 , electrolyte composition and impurities e.g., HF. [24][25][26] Also graphite exhibits different SEI layer compositions on plane and edge sites.…”
mentioning
confidence: 99%
“…sXAS spectra are sensitive to the unoccupied electronic states in the vicinity of the Fermi energy EF. They provide a powerful tool to study the oxidation states, chemical bonds, spin properties and orbital characteristics of the transition-metals involved in battery electrodes [14][15] . Moreover, sXAS is a unique tool that can provide information about both the surface (probe depth of about 10 nm) and the bulk (probe depth of about 100 nm) through the total electron yield (TEY) and total fluorescence yield (TFY), respectively.…”
Section: Introductionmentioning
confidence: 99%